Pengembangan Limbah Biji Asam Jawa (Tamarindus Indica L.) Sebagai Inovasi Produk Bubuk Kopi Khas Sumbawa: Untuk Mengurangi Limbah Biji Asam Jawa Khususnya di Kabupaten Sumbawa - Abdillah, Rijal Fauzan; Anam Afgani, Chairul (Faculty of Agriculture Science & Technology, 2025)
Asam (Tamarindus indica L.) or also known as tamarind is a fruit that grows in the Sumbawa region. In Sumbawa, tamarind fruit is often used as a seasoning for dishes such as sepat, singang and ikan bage. Besides, tamarind also produces waste that is not utilized properly, one of which is tamarind seeds. Therefore, one innovation to reduce tamarind seed waste is to make it into a coffee powder product. The purpose of this study was to found a tamarind seed-based beverage formulation as a substitute for coffee beans without changing its taste and properties. This type of research is laboratory-based experimental consisting of 4 treatments of coffee powder with variations in roasting time (5, 10, 15 and 20 minutes). The parameters tested were tannin content, water content test, and sensory quality test by scoring and hedonic. Based on the results of the study, the sensory quality test on the parameters of color, smoothness, aroma and taste with the highest treatment was found in the fourth treatment. The scores were (4.50), (3.97), (4.23), (4.27) and hedonic scores were (3.73), (3.97), (4.17), (3.43). In the water content test, the highest treatment was found in the fourth treatment with a value of 4.59%, which has fulfilled SNI 01-3542-2004, which is a maximum of 7%. In the tannin content test, the fourth treatment was the highest treatment with a value of 0.017%. The results showed that the best treatment was the fourth treatment with a roasting time of 20 minutes. Keywords: Tamarind Seeds, Coffee Beans, Moisture Content, Tannin Content